2011
DOI: 10.1128/jvi.02154-10
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyopathy Syndrome of Atlantic Salmon (Salmo salar L.) Is Caused by a Double-Stranded RNA Virus of the Totiviridae Family

Abstract: Cardiomyopathy syndrome (CMS) of farmed and wild Atlantic salmon (Salmo salar L.) is a disease of yet unknown etiology characterized by a necrotizing myocarditis involving the atrium and the spongious part of the heart ventricle. Here, we report the identification of a double-stranded RNA virus likely belonging to the family Totiviridae as the causative agent of the disease. The proposed name of the virus is piscine myocarditis virus (PMCV). On the basis of the RNA-dependent RNA polymerase (RdRp) sequence, PMC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
212
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(226 citation statements)
references
References 39 publications
13
212
1
Order By: Relevance
“…Sequencing revealed that both isolates from wild salmon were > 99% similar to the PMCV genome sequence reported by Haugland et al (2011) (GenBank accession numbers JQ745675-JQ745680). Using this genome as a reference, Isolate 1198 had a partial ORF3 se quence that was identical to the reference genome, but in both isolates a small number of unique single nucleotide differences were detected in the other 2 ORFs.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Sequencing revealed that both isolates from wild salmon were > 99% similar to the PMCV genome sequence reported by Haugland et al (2011) (GenBank accession numbers JQ745675-JQ745680). Using this genome as a reference, Isolate 1198 had a partial ORF3 se quence that was identical to the reference genome, but in both isolates a small number of unique single nucleotide differences were detected in the other 2 ORFs.…”
Section: Resultsmentioning
confidence: 88%
“…This was based on the presence of eosinophilic inclusions in nuclei of myocardial fibres in the vicinity of degenerated areas. Experimental transmission studies have supported this hypothesis (Bruno & Noguera 2009, Fritsvold et al 2009, and in 2010 a doublestranded RNA virus tentatively of the Totiviridae family was described as the causative agent of CMS (Løvoll et al 2010, Haugland et al 2011.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Similarly, viral haemorrhagic septicaemia (VHS) was irst reported in the early 1950s in salmonids while the causative agent was characterized later after 10 years in 1962 [24]. This trend was observed for several other diseases such as infectious hematopoietic necrosis virus (IHNV), nervous necrosis virus (NNV), heart and skeletal muscle inlammation (HSMI) and cardiac myopathy syndrome (CMS) in which identiication of the etiological agents took long after clinical signs were irst reported [25][26][27][28][29][30][31][32][33]. However, the upcoming of metagenomics has accelerated our discovery of novel pathogens in which the duration from observation of irst clinical signs to identiication of the etiological agent has been reduced.…”
Section: Application Of Metagenomics In Diagnostics and Discovery Of mentioning
confidence: 87%
“…For example, infectious pancreatic necrosis (IPN) was removed as an OIE notifiable disease of aquatic animals in 2005 but IPN continues to cause losses to the aquaculture industry in Europe [15,86]. Examples of recently identified diseases include cadiomyopathy syndrome (CMS) [43], and hemorrhagic kidney syndrome (HKS) involving Toga-like virus in Atlantic salmon [11]. Another example of a recently identified virus that has been implicated in increased mortality in barbel fry (Barbus barbus) in Hungary includes a circovirus (single-stranded DNA containing virus) although a relation between the presence of the virus and clinical manifestations has yet to be established [65].…”
Section: Viral Diseases Of Farmed Finfishmentioning
confidence: 99%